Incest as an example of a conflict between natural law and positive law - Okoński, Jan (Acta Universitatis Lodziensis. Folia Iuridica, 2018)
This paper discussed incest as an example of a dispute between natural and positive law. An analysis of Art. 201 of the Polish Penal Code was conducted through the prism of legal goods, which, according to the doctrine, Art. 201 is supposed to protect. The article assessed the prohibition of incest as a kind of legal and natural norm, both from the point of view of the classic, maximalist concept of natural law and H.L.A. Hart’s minimum content of natural law. The article then refers to a significant lack of universality of penalization of this phenomenon across legislations of other European states. The author assumed that the Polish statutory penalization of incest met the conditions of the concept of the minimum content of natural law. Therefore, it may be treated as an expression of the legislator’s acceptance of the protection of moral principles, which are present in Polish culture.